Measuring adaptation progress across scales and time frames (International Platfom for Adaptation Metrics -IPAM) - Grosjean, Godefroy; Nowak, Andreea C. (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Presentation for the Agriculture Committee of the International Platfom for Adaptation Metrics (IPAM), April 7 2021. This provides an overview of select adaptation metrics for the agriculture metrics, mapped as part of the reference system.